Collaborative processes in learning and research communities : A narrative and dialogic approach - Tietsche, Claudia; Caetano, Ana Paula (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The article focuses on understanding the development of learning communities, reflecting on collaborative processes in two research groups. It corresponds to an experience account, crossing the eyes of the two authors during an doctorate internship in Lisbon, accomplished by the first and supervised by the second. Actions of acceptance, belonging and sharing are evident, but also conflicts arising from cultural differences between individuals and groups. In the very co-construction of this article, which involved the confrontation and complementarity of narrative testimonies of the same and different situations, an intersubjective and dialogic process is assumed in the construction of knowledge.